Validitas dan Realibiltas Skala General Health Questionare-12 (GHQ-12) untuk Deteksi Distres Psikologis pada Individu yang Mengalami Quarter-life Crisis di Indonesia. - Balqis, Audita Izza (Journal of Research and Measurement in Psychology: JPPP, 2025)
This study aims to test the validity and reliability of the General Health Questionnaire-12 (GHQ)-12) for the Indonesian version, specifically for individuals who experience a quarter-life crisis. Individuals who experience a quarter-life crisis are identical in the form of psychological distress. The development of the GHQ-12 instrument was carried out to facilitate professionals in detecting levels of psychological distress as well as as an instrument in providing appropriate treatment. 300 participants (M= 23.70; SD = 2.64) were involved in this study. The reliability of Cronbach's Alpha (α=0.903) showed GHQ-12 as an acceptable instrument. The GHQ-12 was found a one-dimensional model. CFA with goodness of-fit was found GHQ-12 was accepted, value of X2= 153.893; RMSEA=0.079; GFI=0.921; TLI= 0.918; and CFI=0.933. This study’s results indicate satisfactory validity and reliability for GHQ-12 as an instrument in detecting psychological distress for individuals experiencing a quarter-life crisis. The implications of this study can be used as a reference in providing appropriate interventions for overcoming psychological distress.